Characterization of Cell Cycle-Related Competing Endogenous RNAs Using Robust Rank Aggregation as Prognostic Biomarker in Lung Adenocarcinoma - Yang, Yifei; Zhang, Shiqi; Guo, Li (Frontiers in Oncology, 2022)
Lung adenocarcinoma (LUAD), one of the most common pathological subtypes in lung cancer, has been concerned because of the leading cause of cancer-related death. For the poor prognosis, to identify a prognostic biomarker, this study performed an integrative analysis to screen curial RNAs to discuss their cross-talks. The mRNA profiles were primarily screened using robust rank aggregation (RRA) through several datasets, and these deregulated genes showed important roles in multiple biological pathways, especially for cell cycle and oocyte meiosis. Then, 31 candidate genes were obtained via integrating 12 algorithms, and 16 hub genes (containing homologous genes) were further screened according to the potential prognostic values. These hub genes were used to search their regulators, biological-related miRNAs. In this way, 10 miRNAs were identified as candidate small RNAs associated with LUAD, and then miRNA-related lncRNAs were further obtained. In-depth analysis showed that 4 hub mRNAs, 2 miRNAs and 2 lncRNAs were potential crucial RNAs in the occurrence and development of cancer, and a competing endogenous RNA (ceRNA) network was then constructed. Finally, we identified CCNA2/MKI67/KIF11:miR-30a-5p:VPS9D1−AS1 axis related cell cycle as a prognostic biomarker, which provided RNA cross-talks among mRNAs and ncRNAs, especially at the multiple isomiR levels that further complicated the coding-non-coding RNA regulatory network. Our findings provide insight into complex cross-talks among diverse RNAs particularly involving in isomiRs, which will enrich our understanding of mRNA-ncRNA interactions in coding-non-coding RNA regulatory network and their roles in tumorigenesis.